2010
DOI: 10.1089/acm.2009.0456
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Treatment for Persistent Hiccups in Patients with Cancer

Abstract: Objective The objective of this study was to investigate the effects of acupuncture treatment for persistent hiccups in cancer patients. Design The study design was a retrospective case series. Settings/location The study setting was the Clinical Research Center of the National Institutes of Health. Subjects The subjects were 16 adult male patients ages 27–71 with cancer, with persistent hiccups. Interventions There were one to three acupuncture sessions over a 1–7-day period. Outcome measures Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…As a last resort, surgery could be a solution by blocking the phrenic nerve. Acupuncture has also been reported as an effective treatment in cancer patients [4]. However, the evidence for the treatment of persistent hiccups is mostly based on anecdotal experience and case reports.…”
Section: Discussionmentioning
confidence: 99%
“…As a last resort, surgery could be a solution by blocking the phrenic nerve. Acupuncture has also been reported as an effective treatment in cancer patients [4]. However, the evidence for the treatment of persistent hiccups is mostly based on anecdotal experience and case reports.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] A small study demonstrated efficacy of vinegar nasal instillation in advanced cancer patients with persistent hiccups. 24 Descriptions of behavioral conditioning, hypnosis and even prayer can also be found, but there is no strong evidence for support their indication.…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%
“…Nonpharmacological approaches range from home remedies such as breath holding, to traditional Chinese medicine in the form of acupuncture, to sophisticated techniques such as phrenic nerve block and vagus and/or phrenic nerve stimulation. [27][28][29][30][31]12 In one study, 16 adult male patients with cancer with intractable hiccups underwent acupuncture treatment for their hiccups. 28 Thirteen of these patients had complete resolution of their hiccups, and significant reduction in discomfort, distress, and fatigue were reported.…”
Section: Treatmentmentioning
confidence: 99%
“…[27][28][29][30][31]12 In one study, 16 adult male patients with cancer with intractable hiccups underwent acupuncture treatment for their hiccups. 28 Thirteen of these patients had complete resolution of their hiccups, and significant reduction in discomfort, distress, and fatigue were reported. 28 However, there are theoretical concerns with performing acupuncture in those who are immunocompromised, and the availability to obtain and pay for this treatment is often limited.…”
Section: Treatmentmentioning
confidence: 99%